Dissociation of interleukin-2 production from the cell activation in response to the mitogenic lectin in peripheral CD4+ T cells of LEC mutant rats. - Sakai, T (1993)
A mutant strain of rat, LEC, exhibits a novel maturational arrest of T cells in the thymus, that is, an arrest of the differentiation from CD4+ CD8+ to CD4+ CD8- cells. However, CD4+ T cells were found to arise in lymph nodes (LN) of LEC rats. These CD4+ T cells were T-cell receptor (TcR)/CD3+ and the cross-linking of either TcR alone or both TcR and CD4 molecules induced [3H]thymidine deoxyribose (TdR) incorporation, similar to functional CD4+ T cells. Stimulation with a T-cell mitogen, concanavalin A (Con A), also induced the [3H]TdR incorporation and interleukin-2 receptor (IL-2R) expression in LEC rat CD4+ T cells. Nevertheless, Con A stimulation did not induce IL-2 production by these cells. However, when the stimulation signals were bypassed by ionomycin and phorbol 12-myristate 13-acetate (PMA), IL-2 was normally produced, suggesting that the IL-2 gene and nuclear factors for the IL-2 gene transcription are normal in LEC rats. These results suggest that signals induced by Con A are separated into the one for IL-2 secretion and the other for cell activation including DNA synthesis and IL-2R expression, and that the former signal transduction is blocked in LEC rat CD4+ T cells. Thus, CD4+ T cells in LEC rat LN might provide a good tool for investigating the regulatory mechanisms of IL-2 production.